O původu a zdrojích proměn české podnikatelské elity - Benáček, Vladimír (Lidé města, 2008)
Based on the Czech experiences from the post-communist reforms, the aim of the paper is to shed light on why the early stages of transition in all post-communist societies offered so many opportunities to nomenclature and why the access to capital ownership could not avoid asset stripping. Special attention is given to the corrective processes of economic re-adjustments when the social order converges gradually to a more standard capitalist organization. The main characteristics of these evolutionary processes were: parallel restructuring at economic, political, social a legal levels; high speed of corrections notwithstanding the detours on the path; non-violence in domestic negotiations. The European Union played a very important disciplining role in that respect. In the Czech case, we have identified four groups involved in the run for a position among the new entrepreneurial elite. The initially large gains of the nomenklatura gradually eroded when new businesses opened to international competition, with a parallel increase in endowments of human (entrepreneurial) and economic capitals. As a result, the former nomenklatura was partially squeezed out of the tradable sector, which was occupied by better-skilled foreign and domestic entrepreneurs. The exiting entrepreneurs partially defected to sectors less open to competition, where the alignment with social capital and bureaucracy retained its power. Their future position depends on the pending reforms of public administration and on the search for a more efficient social model.